Flying onto global minima on potential energy surfaces: A swarm intelligence guided route to molecular electronic structure. Issue 5 (12th November 2016) - Shukla, Rishabh; Ray, Debmalya; Sarkar, Kanchan; Kumar Dixit, Mayank; Prasad Bhattacharyya, Shankar
Abstract : A novel quantum‐classical recipe for locating the global minimum on the potential energy surface of a large molecule and simultaneously predicting the associated electronic charge distribution is developed by interfacing the classical particle swarm optimization with a near optimal unitary evolution scheme for the trial one electron density matrix. The unitary transformation is generated by an antihermitian matrix linked to the molecular electronic Hamiltonian at the instantaneous nuclear configurations discovered by the swarm as it flies. The algorithm is used to predict the extensive reorganization of electronic charge distribution and bond lengths in polythiophene oligomers on doping at various levels. Abstract : A novel quantum‐classical recipe for locating the global minimum on the potential energy surface (PES) of a large molecule, while simultaneously predicting the associated electronic charge distribution, is developed by interfacing the classical particle swarm optimization with a near optimal unitary evolution scheme for the trial one electron density matrix. The proposed method provides a viable soft computing alternative to more traditional search for the minimum energy molecular electronic structure on a complex PES.